Respostas
respondido por:
0
2x² + 2y² + 8x - 12y - 6 = 0
x² + 4x + y² - 6y - 3 = 0
x² + 4x + 4 - 4 + y² - 6y + 9 - 9 - 3 = 0
(x + 2)² + (y - 3)² = 4 + 9 + 3 = 16
equação de uma circunferencia
(x + 2)² + (y - 3)² = 16
centro C(-2,3) e raio 4
x² + 4x + y² - 6y - 3 = 0
x² + 4x + 4 - 4 + y² - 6y + 9 - 9 - 3 = 0
(x + 2)² + (y - 3)² = 4 + 9 + 3 = 16
equação de uma circunferencia
(x + 2)² + (y - 3)² = 16
centro C(-2,3) e raio 4
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás